Micro Analysis Of The Cultural Topics In The English Foreign Language Textbook: The Case Of “new Prospects” For Third Year Secondary School Level In Algeria - Mouloud, Ait Aissa; Chami, Wahid Hamza Mohamed (جامعة الوادي - University of Eloued, 2020)
The present study is concerned with the microanalysis of the cultural topics in the in-use Algerian English foreign language textbook “New Prospects” which is designed for third-year secondary school students. It aims at exploring the distribution of the types and categories of culture in the target textbook. The study is conducted through a quantitative approach. The content analysis is operated as a research tool with the target textbook. The main results of the study show some dominance of big “C” culture and non-target cultural materials over small “c” culture and target culture. On the basis of the results, pedagogical implications and recommendations are suggested to remedy the existing cultural deficiencies in the textbook. تهتم الدراسة الحالية بالتحليل الجزئي للمواضيع الثقافية المستخدمة في كتاب اللغة الإنجليزيةفي قسم اللغة الانجليزية الذي يحمل عنوان "آفاق جديدة" “New Prospects”والذي تم تصميمه خصيصا لطلاب السنة الثالثة لطور الثانوي. تهدف إلى استكشاف توزيع أنواع وفئات الثقافة في الكتاب المدرسي المستهدف. وتجرى الدراسة من خلال المنهج الكمي الذي يعتمد على تحليل المحتوى كأداة بحث مع الكتاب المدرسي المستهدف وقد أظهرت النتائج الرئيسية للدراسة نوعا من الهيمنة للثقافة الكلية على الجزئية وكذلك الثقافة المحلية على الثقافة المستهدفة. وعلى أساس هذه النتائج، تقترح الدراسة مجموعة من التوصيات التربوية لمعالجة أوجه القصور الثقافي الموجودة في الكتاب المدرسي. الكلمات المفتاحية: الثقافة واللغة ، الثقافة الكلية ، الثقافة الجزئية، الثقافة المستهدفة، الثقافة المحلية، كتاب اللغة الإنجليزية كلغة أجنبية، تحليل المحتوى الثقافي.
مقال
Keywords: Big “C” and Small “c” Culture ; Target and Source Culture ; Thematic Analysis ; EFL Textbook ; Micro Analysis